PEMBUATAN STORYLINE VIDEO DOKUMENTER SEBAGAI UPAYA PELESTARIAN PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE (PSHT) DI KOTA MADIUN - Marsha Asyafa Fanani; Diana Aqidatun Nisa; Bayu Setiawan (JURNAL IMAJINASI, 2024)
Its culture is so vast, thus worthy of preservation for the younger generation to prevent Indonesian culture from easily disappearing. Indonesia is a unified nation that cherishes its culture and traditions. The Brotherhood of Setia Hati Terate (PSHT) is one of the leading schools of Pencak Silat in Indonesia, founded by Ki Ngabehi Surodiwiryo, a renowned martial arts figure who also pioneered the Setia Hati (SH) style of Pencak Silat in the early 19th century. The Brotherhood of Setia Hati Terate (PSHT) is known as the most comprehensive silat institution because it integrates five fundamental aspects: spiritual, self-defense, art, sport, and mental discipline. Designing a documentary video to preserve Pencak Silat within the Brotherhood of Setia Hati Terate (PSHT) in Madiun is a fitting and intriguing endeavor to impart knowledge about Pencak Silat within that context. The methodology employed in this design is both qualitative and quantitative, utilizing various approaches such as interviews, observations, questionnaires, and literature review. The resulting keyword, "Harmony of Cultural Brotherhood," can be interpreted as the depiction of harmony within the context of cultural fraternity. Moreover, it serves as an effort for introduction, exploration, and learning about one of the cultural heritages, Pencak Silat, within the Brotherhood of Setia Hati Terate (PSHT), for the future development of this traditional martial art while simultaneously enhancing the image and value of Pencak Silat. The medium for this design is a documentary video aimed at preserving Indonesian cultural heritage, including the martial art of Pencak Silat within the Brotherhood of Setia Hati Terate (PSHT).